WTO reform and China: Defining or defiling the multilateral trading system? - GAO, Henry S. (Institutional Knowledge at Singapore Management University, 2021)
In November 2001, China finally acceded to the World Trade Organization, in a deal described by then WTO Director-General Mike Moore as a “defining moment in the history of the multilateral trading system”. In recent years, however, China has been accused of defiling the letter and spirt of WTO rules with its unique economic model. Believing that existing WTO rules are inadequate in dealing with the China challenge, key WTO Members have launched a new round of WTO reform, which is the subject of this article. Contrary to popular belief, most of the problems concerning China are not new but reflect long-standing issues in China’s economic system which predate the WTO accession. Thus, the article starts by tracing China’s long and storied history with the GATT and WTO, highlighting the key commitments designed to alleviate the perceived problems with China’s unique economic system. The next part discusses China’s limited role in the ill-fated Doha Round, the first and only negotiating round ever officially launched by the WTO. This is followed by a comprehensive and in-depth analysis of the main issues in the current discussions on WTO reform, a process that started at the last WTO Ministerial Conference held in December 2017. In particular, the paper examines in detail the efforts by some major players to turn it into a so-called “China Round”, and China’s reactions. The paper concludes with a review of the failed attempt of the US to address some of these issues through the trade war, and suggests that multilateral negotiation is the best way forward.